Black hunger : soul food and America - Witt, Doris (University of Minnesota Press, 2004)
Black Hunger focuses on debates over soul food since the 1960s to illuminate a complex web of political, economic, religious, sexual, and racial tensions between whites and blacks and within the black community itself. Doris Witt draws on vaudeville, literature, film, visual art, and cookbooks to explore how food has been used both to perpetuate and to challenge racial stereotypes.